1998
DOI: 10.1136/gut.43.6.752
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome after infection with Helicobacter pylori does not appear to be reliably predicted by the presence of any of the genes of the cag pathogenicity island

Abstract: Background-The development of clinical disease after infection with Helicobacter pylori has been reported to be associated with expression of the cagA gene. Recently, it has been shown that cagA is part of a multigene locus, described as the cag pathogenicity island (PAI). The role of this region in determining clinical outcome remains to be established. Aims-To investigate whether the presence of cagA is always associated with the presence of the complete cag PAI and to evaluate the distribution of selected c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
101
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(121 citation statements)
references
References 36 publications
(28 reference statements)
14
101
6
Order By: Relevance
“…Nevertheless, our study suggested that positive rate of cagG in H pylori was high and cagG was quite conservative in Chinese population, and that there was no difference in the frequencies of cagG-positive isolates among patients with gastritis, duodenal ulcer, gastric ulcer or gastric duodenal ulcer. Our results are supported by the study by Jenks et al [20] who demonstrated that no specific genes within the cag PAI could reliably predict the clinical outcome of H pylori infection in French patients, and also by Hsu et al [17] who concluded that any of the cag PAI genes such as cagE could not predict the clinical presentation in Korean patients.…”
Section: Discussionsupporting
confidence: 80%
“…Nevertheless, our study suggested that positive rate of cagG in H pylori was high and cagG was quite conservative in Chinese population, and that there was no difference in the frequencies of cagG-positive isolates among patients with gastritis, duodenal ulcer, gastric ulcer or gastric duodenal ulcer. Our results are supported by the study by Jenks et al [20] who demonstrated that no specific genes within the cag PAI could reliably predict the clinical outcome of H pylori infection in French patients, and also by Hsu et al [17] who concluded that any of the cag PAI genes such as cagE could not predict the clinical presentation in Korean patients.…”
Section: Discussionsupporting
confidence: 80%
“…Ahmadzadeh et al represented 13 different cagPAI genotyptes among 21 cagPAI positive H. pylori strains in Iran (34).This diversity is also high in different geographic populations (11,(35)(36)(37). Correlation between integrity of cagPAI, types of EPIYA motifs, and disease outcome was confirmed by several studies (24,(38)(39)(40)(41)(42). However, there are studies that reported contrary results (43)(44)(45).…”
Section: Discussionmentioning
confidence: 56%
“…In addition, Day et al [36] detected that 12 out of 13 children (92%) with duodenal ulcers were infected with Cag E-positive isolates, compared with only 5 out of 16 (31%) with gastritis alone. Although French study found that 51 out of 56 (91%) strains isolated from patients with duodenal ulcers were Cag E-positive, whereas 13 out of 17 (76%) H. pylori isolates obtained from patients with gastritis alone were positive but with non statistically significant difference between duodenal ulcer and gastritis patents [37]. This difference was explained as different geographic location of the patients may affect the results of the studies.…”
Section: Discussioncontrasting
confidence: 38%